Developing a climate adaptation tracking system for Kenya and Ethiopia - Njuguna, Lucy (International Livestock Research Institute, 2024)
To support countries in Eastern Africa to track their adaptation actions in the livestock sector, the CGIAR Research Initiative on Livestock and Climate worked with Kenyan and Ethiopian stakeholders in the development of a tracking tool called TAiLS (Tracking Adaptation in Livestock Systems). This was accompanied by a purposeful influencing of international discourse on adaptation actions in the livestock sector, through actively promoting the experience of developing the tracking tool across the climate adaptation community in which previously adaptation tools were more focused on crop agriculture.